BUILDING CHARACTER OF HARDINESS THROUGH RELIGIOUSITY AND LOCAL WISDOM FOR MERCHANT MARINE CADET IN ACEH, INDONESIA - Subiyantoro subiyantoro; Mangun Budiyanto; Budi Riyanto; Buyung Surahman (Universitas Ahmad Dahlan, 2021)
This study aims to describe the model of character building of prospective marine transportation cadets in Malahayati Merchant Marine Polytechnic, Aceh, Indonesia. The research method used in this study was a qualitative method using a phenomenological research design. Through participatory action research, in-depth interviews, observation, and documentation, the data were found, which Miles and Huberman's model used as data analysis. The data analysis process consisted of data reduction, data display, drawing conclusion/verification. The research result showed that character educational implementation of Merchant Marine Education in Aceh was conducted through (1) the instruction method, education, suggestion, persuasion, trusting, punishment, guidance and counseling, Habituation, group discussion, and organizational activities. The method implementation adjusted to the activities and educational cadet level starting from prospective cadet to senior cadet. (2) Method implementation intervention conducted through the hidden curriculum like moral knowing, moral feeling, moral action, and religiosity that manifests in five diversity dimensions: religious belief, religious practice, religious feeling, religious knowledge, and religious effects. (3) Attitude nurture implementation conducted through local wisdom habituation that includes exemplary figures of leaders/coach/trainers/senior cadets, behavioral standards, and reflection studies. (4) Religious character educational implementation bears a resilient cadet profile who is smart, professional, skilled, and good. This research finding recommended the importance of religiosity and local wisdom in building the character of Hardiness.